Bonney's gynaecological surgery - Bonney, Victor 1872-1953; Lopes, Tito; Spirtos, Nick; Naik, Raj; Monaghan, John M. (Wiley-Blackwell, 2011)
This comprehensive new edition covers all major procedures in gynecological surgery. Providing a clear description of the basic surgical instrumentation and techniques, this well-illustrated book presents recent developments including minimally invasive and laparoscopic surgery.